2010
DOI: 10.1183/09031936.00118009
|View full text |Cite
|
Sign up to set email alerts
|

Infant swimming in chlorinated pools and the risks of bronchiolitis, asthma and allergy

Abstract: Recent studies suggest that swimming in chlorinated pools during infancy may increase the risks of lower respiratory tract infection. The aim of the present study was to assess the influence of swimming in chlorinated pools on the risks of bronchiolitis and its late consequences.A total of 430 children (47% female; mean age 5.7 yrs) in 30 kindergartens were examined. Parents completed a questionnaire regarding the child's health history, swimming practice and potential confounders.Attendance at indoor or outdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
1
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 32 publications
3
58
1
10
Order By: Relevance
“…To build such predictive models, we should use the risk factors for asthma known in the existing literature [234][235][236][237][238][239] rather than only those for bronchiolitis patients. As one predictive model does not fit all, we should develop separate predictive models for children presenting with bronchiolitis at <6, 6-12, and 13-24 months of age [240].…”
Section: Predicting Whether a Bronchiolitis Patient Will Later Be Diamentioning
confidence: 99%
“…To build such predictive models, we should use the risk factors for asthma known in the existing literature [234][235][236][237][238][239] rather than only those for bronchiolitis patients. As one predictive model does not fit all, we should develop separate predictive models for children presenting with bronchiolitis at <6, 6-12, and 13-24 months of age [240].…”
Section: Predicting Whether a Bronchiolitis Patient Will Later Be Diamentioning
confidence: 99%
“…Recently, a study conducted by Voisin et al has shown that swimming in indoor and outdoor pools during infancy is associated with a dosedependent increase in the risk of bronchiolitis. This effect independent of other risk factors as exposure to tobacco or smoke, day-care attendance or antecedents of atopic diseases and could increase the risk of asthma and respiratory allergies later during childhood [76].…”
Section: The "Chlorine Hypothesis"mentioning
confidence: 99%
“…It was shown that attendance at chlorinated pools before the age of 2 years was associated with an increased risk of bronchiolitis, and infant swimmers who developed bronchiolitis had a higher risk of asthma and respiratory allergies later in childhood. 5 Environmental tobacco smoke is one of the strongest predictors of chronic respiratory illness in children, including the development of asthma. There are now data that show that in utero smoke exposure can increase airway responsiveness to methacholine among children with asthma.…”
Section: Exposuresmentioning
confidence: 99%